Black phosphorous nanosheets: prospective field emitter - Late, Dattatray J.; Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We report for the first time field electron emission investigations on few layered black phosphorous nanosheets emitter's synthesized using chemical method with thickness similar to 2-5 nm. The turn-on electric field required to draw an emission current density of similar to 10 mu A/cm(2) was found to be similar to 4.2 V/mu m. Furthermore, a few layer black phosphorous nanosheets emitter deliver an large emission current density of similar to 170 mu A/cm(2) at an applied field of similar to 7.5 V/mu m. The emission current versus time plot measured at the preset current values of similar to 5 mu A shows field emission current fluctuations within +/- 10% of the average value indicating the well stable nature of black phosphorous field emitter. Thus, the two dimensional black phosphorous nanosheets synthesized using simple electrochemical exfoliation method can be realized and utilized for the next generation micro/nanoelectronics and flat panel field emission based display applications.